Well-arranged novel InGaN hexagonal nanoplates at the tops of nitrogen-polarity GaN nanocolumn arrays - Tetsuya Kouno (AIP Advances, 2012)
Periodically arranged novel InGaN hexagonal nanoplates were fabricated at the tops of square-lattice N-polarity GaN nanocolumn arrays. The key finding in this work is that the growth of InGaN on N-polarity GaN nanocolumns led to a peculiar nanoplate structure. The InGaN nanoplates with thicknesses of 50-100 nm extended outward from the narrow nanocolumns with diameters of 100-150 nm, to form larger hexagonal nanoplates with a typical side length of 250 nm.